Do elites benefit from democracy and foreign aid in developing countries? Comment - Henrik Hansen; Louise Lund Rants; Julie Buhl-Wiggers (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2009)
In the study 'Do elites benefit from democracy and foreign aid in developing countries' (Journal of Development Economics, 2009) Bjørnskov asks if political elites benefit from foreign aid relative to the rest of the population. He concludes that his results provide qualified support for the hypothesis by indicating that foreign aid is positively associated with elites' share of total income in democratic developing countries, but not particularly so in autocracies. Based on the regressions presented in Bjørnskov's paper, we show that this conclusion is questionable. Foreign aid is not significantly associated with income redistribution in democratic developing countries.
Keywords: D31; F35; 330; Inequality; Foreign Aid; Democracy; Entwicklungshilfe; Gesellschaftsordnung; Demokratie; Elite; Einkommensumverteilung; Entwicklungsländer